The identity of Ranunculus laohegouensis (Ranunculaceae) from Sichuan, China - Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2017)
We demonstrate that Ranunculus laohegouensis (Ranunculaceae) described from Pingwu in northwestern Sichuan, China, is conspecific with R. sinovaginatus, a species previously already recorded to occur in northwestern Sichuan. We therefore place the former in synonymy within the latter.